Tensile behavior of the titanium-steel explosive welded interface under quasi-static and high-strain rate loading. (1st November 2022) - Zhou, Qiang; Liu, Rui; Zhou, Qiang; Fan, Keshe; Xie, Jing; Chen, Pengwan; Rittel, Daniel
Abstract: Explosive welding is well known for its capability to join a wide variety of both similar and dissimilar metals. The strengths of the welded composite plates are largely influenced by the bonding strengths of the welding interfaces, which generally exhibit a periodic wavy shape. The measurement of the tensile properties of the bonding interface is challenging due to the difficulties in preparing conventional direct tensile specimens arising from the millimeter-sized thickness of the flyer plate. In this paper, a novel small-sized (15 mm × 14 mm × 8 mm) double- T -shaped specimen was designed to study the tensile properties and failure mechanisms of the titanium/steel bonding interface, in which a clamping apparatus was used to apply compressional load on the specimen to generate tensile stress. The quasi-static (∼0.001/s) tension was conducted using the Instron MTS and the high strain rate (2000–5000/s) tension was performed using the split Hopkinson pressure Bar apparatus. Further, the microstructure of interfacial zone was characterized by optical microscopy, scanning electron microscopy and energy dispersive spectrometer. The experimental results indicated that the interface strength increased with increasing strain rate, showing an obvious positive strain rate effect. The fluctuation in tensile strengths and failure strain of the titanium/steel bonding interface were due to the presence of non-uniform defects, (e g. cavities, cracks and brittle intermetallic etc.) formed on the bonding interface. Those defects as discontinuities and stress concentration points would result in degraded mechanical properties. The fracture morphology mainly reveals brittle fracture under quasi-static, while ductile fracture existed in some zone at high strain rate. Failure mainly occurred in the bonding interface near the steel side from the interface, which showed microcracks, cleavage plane, tearing ridges, dimples, fragmentation of brittle intermetallic compounds. Meanwhile, the double- T -shaped specimen has proven to be effective to measure the tensile mechanical properties of the interface of materials with small thickness.